1076. Gaps in Measles and Mumps Seroprevalence Among Cancer Patients. (31st December 2020) - Marquis, Sara; Logue, Jennifer; Loeffelholz, Tillie; Quinn, Z Z; Liu, Catherine; Stewart, Marc; Chu, Helen Y; Pergam, Steven A; Krantz, Elizabeth M
Abstract: Background: Immunosuppressed cancer patients are at risk for morbidity and mortality from vaccine preventable diseases. Recent outbreaks and declining vaccination rates put cancer patients at increased risk for measles and mumps exposures. To assess the current status within our center, we measured measles and mumps seroprevalence among cancer patients. Methods: Residual clinical plasma samples from patients seen at Seattle Cancer Care Alliance were collected between 8/11/2019 and 8/15/2019 and tested for measles and mumps IgG using ELISA (Genway Biotech); patients receiving intravenous immunoglobulin ≤16 weeks prior to collection date were excluded. Seroprevalence was calculated based on positive results; equivocal results were not considered protective. Demographic and clinical data were abstracted from medical records. Overall and subgroup seroprevalence were estimated with Wilson 95% confidence intervals (CI); Poisson regression with robust standard errors was used to compare subgroups and estimate prevalence ratios (PR). Results: Of 1000 unique patients, 987 were eligible, with a median age of 61 years (range 2-97). More than half had a solid tumor (574 [58%]) while 376 (38%) had a hematologic malignancy (HM); 155 (16%) were hematopoietic cell transplant (HCT) recipients. The percentage of seropositive patients was 75% (95% confidence interval [CI]: 72%, 78%) for measles and 62% (95% CI: 59%, 65%) for mumps. Seropositivity was highest among older age groups, particularly those older than 63, who most likely have naturally acquired immunity (Figure 1-2). In multivariable analysis, patients aged 30-59 years were significantly less likely to be seropositive compared to patients ≥80 years of age. Patients with HM and those undergoing HCT were also less likely to be seropositive (Figure 3). Figure 1. Distribution of age at sample collection and measles antibody test results Figure 2. Measles and mumps seroprevalence by age Figure 3. Multivariable model estimates for measles and mumps seroprevalence Conclusion: One-quarter of cancer patients tested did not have evidence of seroprotection for measles and mumps. Seronegative and equivocal responses were observed primarily among younger patients and those with hematologic malignancies. Deficits in protective antibody seen in this study are common among cancer patients and underscore the need for population/community-based efforts to increase herd immunity and protect vulnerable populations. Disclosures: Helen Y. Chu, MD MPH, Cepheid (Grant/Research Support)Ellume (Grant/Research Support)Glaxo Smith Kline (Consultant)Merck (Consultant)Sanofi-Pasteur (Grant/Research Support) Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)